1997
DOI: 10.1007/s007050050089
|View full text |Cite
|
Sign up to set email alerts
|

Immunological detection of the 8K protein of potato virus X (PVX) in cell walls of PVX-infected tobacco and transgenic potato

Abstract: Open reading frame 4 (ORF4) of the potato virus X (PVX) genome encodes an 8K protein which is a part of the "triple gene block" and is known to play a role in the cell-to-cell movement of the virus in infected plants. To locate the 8K protein and further elucidate the mechanism of cell-to-cell transport of PVX, antibodies were raised against the 8K protein and used to localize this protein in PVX-infected tobacco and in transgenic potato plants expressing the 8K protein both by subcellular fractionation and by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
32
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 25 publications
1
32
0
Order By: Relevance
“…Using synthetic peptides derived from the p7 sequence, we have identified three distinct putative domains within the protein. EMSA showed that the central region, from residue 17 to 35 (represented by peptide p7 [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] ), is responsible for the RNA binding properties of CarMV p7. This binding peptide populates a nascent ␣-helix in water solution that is further stabilized in the presence of either secondary structure inducers, such as trifluoroethanol and monomeric SDS, or RNA (which also changes its conformation upon binding to the peptide).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Using synthetic peptides derived from the p7 sequence, we have identified three distinct putative domains within the protein. EMSA showed that the central region, from residue 17 to 35 (represented by peptide p7 [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] ), is responsible for the RNA binding properties of CarMV p7. This binding peptide populates a nascent ␣-helix in water solution that is further stabilized in the presence of either secondary structure inducers, such as trifluoroethanol and monomeric SDS, or RNA (which also changes its conformation upon binding to the peptide).…”
mentioning
confidence: 99%
“…There are viruses that encode multiple MPs, which, in addition, do not fall in the 30K superfamily. The triple gene block of potexviruses encodes three proteins (open reading frames 2-4) that mediate cell-tocell transport, the first one with RNA-binding and NTPase/ helicase activities and the other two with putative membranespanning domains and, in the case of the third, demonstrated cell wall localization (22,23). Carmoviruses are among the smallest known plant viruses; their genome is a singlestranded RNA of ϳ4 kilobases encoding at least five proteins (24,25).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…TGBp2 and TGBp3 both contain stretches of hydrophobic amino acids and are associated with cell wall and membrane fractions both in vivo and in vitro (Donald et al, 1993;Hefferon et al, 1997;Morozov et al, 1990Morozov et al, , 1991NiesbachKlosgen et al, 1990;Solovyev et al, 2000). Using a microinjection and transient expression strategies, TGBp2 was shown to assist the movement of the ribonucleoprotein complex of potexviruses (Lough et al, 1998) and to be capable of increasing the SEL of the plasmodesmata (Tamai & Meshi, 2001).…”
Section: Introductionmentioning
confidence: 99%